Multi-omics analysis of hexaploid triticale that show molecular responses to salt stress during seed germination - Wang, Dongxia; Li, Jiedong; Li, Shiming; Fu, Jiongjie; Liu, Baolong; Cao, Dong (Frontiers in Plant Science, 2025)
The development of a salt-tolerant hexaploid triticale cultivar offers an economical and efficient solution for utilizing marginal land. Understanding how hexaploid triticales respond to salt stress is essential if this goal is to be achieved. A genome-wide association study (GWAS), along with transcriptome and proteome analyses, were used in the present study to determine the molecular responses to salt stress in hexaploid triticale. In total, 81 marker-trait associations for 10 salt-tolerance traits were identified in 153 hexaploid triticale accessions, explaining 0.71% to 56.98% of the phenotypic variation, and 54 GWAS-associated genes were uncovered. A total of 67, 88, and 688 differential expression genes were co-expressed at both the transcriptomic and proteomic levels after 4, 12, and 18 h of salt stress, respectively. Among these differentially expressed genes, six appeared in the coincident expression trends for both the transcriptomic and proteomic levels at the seed germination stage. A total of nine common KEGG pathways were enriched at both the transcriptomic and proteomic levels at 4, 12, and 18 h. After integrating GWAS-target genes with transcriptomics and proteomics approaches that the candidate gene late embryogenesis abundant protein 14 (LEA14) was up-regulated at the transcriptomic and proteomic levels. LEA14 contained important stress-responsive cis-acting regulatory elements that could be dynamically regulated by the binding of transcription factors (TFs). This suggested that LEA14 was a key gene associated with salt tolerance in hexaploid triticale and could respond quickly to salt stress. This study improved understanding about the potential molecular mechanisms associated with hexaploid triticale salt tolerance and contributed to the breeding of salt-tolerant germplasms and the utilization of saline soils.